Evaluation of a Housing First programme for people from the public mental health sector with severe and persistent mental illnesses and precarious housing: Housing, health and service use outcomes. (March 2022) - Dunt, David Robert; Day, Susan Elizabeth; Collister, Laura; Fogerty, Beth; Frankish, Rosie; Castle, David J; Hoppner, Cayte; Stafrace, Simon; Sherwood, Sharon; Newton, J Richard; Redston, Suzy
Aims and context: This paper reports the evaluation of the Doorway program (2015-18) in Melbourne, Australia. Doorway extends the original Housing First (HF) model in providing housing support to people with precarious housing at-risk of homelessness with Serious and Persistent Mental Illnesses (SPMIs) receiving care within Victoria's public mental health system. Doorway participants source and choose properties through the open rental market, and receive rental subsidies, assistance, advocacy and brokerage support through their Housing and Recovery Worker (HRW). The aim of this study is to estimate Doorway's impact on participants' housing, quality of life and mental health service use. Methodology: The study employed a a quasi-experimental study design with a comparison group, adjusted for ten potential confounders. The primary outcome measure was days of secure housing per participant. Secure housing status, health service usage and quality of life (HoNOS) data were extracted from participants' electronic hospital and Doorway records in deidentified, non-reidentifiable form. Analysis for continuous outcome variables was based on multivariate GLM modelling. Results: Doorway housed 89 (57%) of 157 accepted participants. The 157 Doorway participants overall were also housed for significantly more days (119.4 extra days per participant) than control participants, albeit after some delay in locating and moving into housing (mean 14 weeks). There was a significant, positive Doorway effect on health outcomes (all and one dimension of the HoNOS). Doorway participants had significantly reduced length of stay during acute and community hospital admissions (7.4 fewer days per participant) compared with the control group. Conclusion: The Doorway model represents a new and substantial opportunity to house, enhance health outcomes and reduce mental health service use for people with SPMIs from the public mental health sector and at-risk of homelessness.